Shigella and childhood stunting: Evidence, gaps, and future research directions. - Karoun H Bagamian; John D Anderson Iv; Gabriela Blohm; Suzanne Scheele (PLoS Neglected Tropical Diseases)
Early childhood growth deficits have been shown to have lifelong health and economic impacts, yet their connection to one of their underlying causes, diarrheal diseases, has remained difficult to characterize. Identifying the processes and mechanisms that underlie this link has remained a challenge due to the complexity of the relationship and limitations in access to more advanced laboratory methods. In recent years, however, several large-scale, multisite studies have extensively investigated and reported the prevalence, etiology, and impacts of diarrheal diseases in children under 5 years (CU5) in low- to middle-income countries (LMICs). These studies, in combination with several single-site studies, have applied more advanced laboratory methods to uncover the etiology, true prevalence, infection mechanisms, and inflammation biomarkers of diarrheal disease. Of the multiple pathogens that have been shown to be strongly associated with diarrheal disease in CU5, Shigella is one of the more prevalent and impactful of these pathogens. In this narrative review, we highlight key insights from these studies and identify knowledge gaps and directions for future research. According to these studies, Shigella is most commonly detected in toddlers and young children; however, it can cause more severe disease and has a greater impact on linear growth for infants. Shigella often has a stronger relationship to linear growth faltering (LGF) than other enteropathogens, with higher Shigella loads resulting in greater growth deficits. Future studies should employ more Shigella-specific molecular assays and identify diarrheal etiologies using standardized diagnostics to improve child anthropometric and Shigella surveillance. Also, they should focus on uncovering the mechanisms of the relationship underlying Shigella and growth faltering to better characterize the role of asymptomatic infections and intestinal inflammation in this relationship.